Legal Records at Risk A strategy for safeguarding our legal heritage - Cowling, Clare (OBServing Law, 2019)
Why do so few institutions in the legal sector have professional records managers or archivists on their staff? This book is the culmination of a three year project by experienced archivist and records managers on private sector legal records at risk in England at Wales. It summarises the work of the Legal Records at Risk (LRAR) project and its predecessors, diagnoses the problems of preservation of archives in the legal sector in England and Wales and outlines a national strategy for such records.